AI-Driven Personalization in Advertising: Transforming Consumer Engagement through Sustainability and Circular Economy - Bashynska, Iryna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
In this comprehensive exploration, the author delves into the dynamic landscape of advertising, unveiling the transformative fusion of artificial intelligence and personalized marketing strategies. The article meticulously dissects the evolving realm of consumer engagement, highlighting the seismic shift towards sustainability and circular economy principles within contemporary advertising strategies. The author elucidates the formidable potential of AI-driven personalization in reshaping consumer behaviors, emphasizing not just transactional engagements but the alignment of advertising with societal values and environmental stewardship. Drawing from a diverse array of case studies and pioneering strategies employed by brands across industries, the article illustrates how these initiatives resonate with environmentally conscious consumers, redefining the purpose of advertising as a platform for education, advocacy, and empowerment. Utilizing a multifaceted methodology encompassing mixed methods, extensive literature review, and in- depth case study analyses, the author navigates through the intersection of AI-driven personalized advertising and sustainability. The study meticulously scrutinizes the amalgamation of these domains, shedding light on their collective potential in directing consumer engagement towards sustainable practices. However, while showcasing the transformative potential of AI-powered strategies, the article recognizes inherent limitations, such as the dynamic nature of consumer preferences and ethical considerations surrounding data utilization in personalized advertising.